1993
DOI: 10.1210/endo.133.4.8404601
|View full text |Cite
|
Sign up to set email alerts
|

Locally produced angiotensin II induces ovulation by stimulating prostaglandin production in in vitro perfused rabbit ovaries.

Abstract: The present study was undertaken to investigate the role of exogenous and endogenous angiotensin II (Ang II) in ovarian steroidogenesis and production of prostaglandin (PG) in in vitro perfused rabbit ovaries. The addition of 100 or 10 micrograms Ang II at 2-h intervals to the perfusate did not stimulate progesterone production, but significantly stimulated estradiol (E2) production by perfused rabbit ovaries. When the specific antagonist of Ang II, saralasin at 2 x 10(-6) M, was added to the perfusate 30 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
34
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 43 publications
7
34
2
Order By: Relevance
“…Direct evidence for the induction of ovulation by AGT-2 comes from studies with rabbits [17,18]. Rabbits are induced ovulators; therefore, the mechanisms involved in ovulation may differ from those in other mammals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct evidence for the induction of ovulation by AGT-2 comes from studies with rabbits [17,18]. Rabbits are induced ovulators; therefore, the mechanisms involved in ovulation may differ from those in other mammals.…”
Section: Discussionmentioning
confidence: 99%
“…One example is angiotensin II (AGT-2), which induced ovulation in perfused rabbit ovaries [17,18]. Conversely, AGT-2 antagonists inhibit ovulation in rodents, rabbits, and cattle [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Renin-and prorenin-like activities have been shown in bovine follicles [4], and angiotensin-converting enzyme is also present in rat ovarian follicles and CL [5]. Furthermore, evidence has been accumulating that Ang II locally regulates ovulation [6,7], oocyte maturation [6,7], and steroidogenesis [8]. These findings suggest that the ovarian RAS may function independently, or in concert with the systemic RAS, and reg- 1 This study was supported by the Japan-Germany joint research project of the Japan society for the Promotion of Science.…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings have shown that Ang II and ET-1 locally modify the synthesis and secretion of hormones produced in the ovarian follicular cells in an autocrine and/or paracrine manner [5,10,[14][15][16][17]. On the other hand, ANP counteracts the actions of Ang II on intracellular cyclic GMP and Ca 2ϩ concentrations [18,19] and affects steroidogenesis in vivo [20] and in vitro [21,22].…”
Section: Introductionmentioning
confidence: 99%